Rethinking the Guidonian hand for twenty-first-century musicians. Issue 2 (1st July 2017) - Fleet, Paul
The immediate recognition and description of the thirteen enharmonic intervals within an octave is a quest upon which students on popular music degree programmes frequently embark, but which they rarely complete. The problem often lies in a disconnect between the sound heard and the sound recognized when the task is undertaken without recourse to an instrument. During the eleventh century, Guido d'Arezzo used the joints on the hand (phalanges) to help music students recognize and sing intervals from hexachords. This article considers rethinking this tool with regard to recent investigations into corporeal intentionality. The approach is developed across three short incremental exercises that are designed for the twenty-first-century musician. It begins by connecting the familiar singing of a major scale whilst pointing to the phalanges of the hand, moving towards inflecting the scale by singing and pointing to non-sequential intervals.